A Study of Local Rice Cultivars from Krayan Grown in Tidal Swam Area - Rusdiansyah Rusdiansyah; Tjatjuk Subiono (International Journal of Science and Engineering, 2014)
The research was conducted in tidal swamp area of Tuak river, Paser Regency. The objective of the research was to obtain rice cultivar with high adaptability and yield grown in tidal swamp area. The study used four local rice cultivars of Krayan i.e. Nanung, Kelabit, Black Adan and White Adan. As a comparison, Yellow Serai was used. The rice was seeded in 5 x 7 m plot with a planting distance of 30 x 30 cm and 1 seed per planting hole. The treatment was replicated three times in a randomized block design. The result showed that all the four cultivars of Krayan had higher height than Yellow Serai. Nanung was found to be the most tolerant cultivar to salinity and the most adaptable in tidal swamp area. Nanung also produced the highest number of rough rice, the highest yield of weight per 1000 grains, the highest yield of weight of milled rice/ha and the least percentage of empty rough rice/panicle i.e. 182 grains, 29.35 g, 4.20 t/ha, and 15%, respectively.